Characteristic of gross pollutants and evaluation of groos pellutans traps (GPTS) in Perlis - Gressi Anak Rigum (School of Environmental Engineering University Malaysia Perlis, 2011)
Gross pollutant traps (GPTs) is a structural controlled device used as an early pretreatment for water especially in open channel. GPTs detained rubbish such as leaf, plastics, polystyrene , paper and sediment to reduce water pollution before it entering the main river. It is usually construct in an open channel with flow from several sources, and end to the outlet which is the river. The objective of this study is to characterize the pollutant traps in the GPTs accordingly and to monitor the water quality of watre before and after the GPTs. From the observation and finding, an improved GPTs design is proposed. The method applied during the study are including weighing the rubbish and sediment collected, water quality monitoring and laboratory analysis and designing a better GPTs system.